Vanishing White Matter With Hepatomegaly and Hypertriglyceridemia Attacks. (November 2013) - Unal, Ozlem; Ozgen, Burce; Orhan, Diclehan; Tokatli, Aysegul; Hismi, Burcu Ozturk; Dursun, Ali; Coskun, Turgay; Kalkanoglu-Sivri, H. Serap
Vanishing white matter disease is one of the most prevalent leukodystrophies in childhood. It is caused by mutations in any of the genes encoding the 5 subunits of the eukaryotic translation initiation factor 2B (eIF2B), EIF2B1 through EIF2B5. Phenotypic variation is wide and it may affect people of all ages. Here we present a child with vanishing white matter who had hepatomegaly and hypertriglyceridemia attacks along with neurologic deterioration episodes. He was found heterozygous for the 2 mutations c.817 A>C, p.Lys273Gln and c.939_948del, p.Asp314ProfsX23 in the gene EIF2B2. Until today, this association was not defined in the literature.